2015
DOI: 10.1002/lno.10162
|View full text |Cite
|
Sign up to set email alerts
|

Deep dynamic pools of phosphorus in the sediment of a temperate lagoon with recurring blooms of diazotrophic cyanobacteria

Abstract: The storage and release of phosphorus by sediments can act as an important control on the formation of noxious blooms of cyanobacteria in lakes and estuaries. Here we studied the uptake and release of phosphorus associated with iron oxides within sediments of a lagoon system affected by recurring summer blooms of the cyanobacterium Nodularia spumigena. Using an ascorbate extraction, we observed deep pools of iron oxide associated phosphorus (P) at concentrations of 5 lmol g 21 dry sed to a depth of 20 cm. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Site S3 was chosen for an in-depth study of the relationships between the variables. Unlike lakes and estuaries, hypoxia and anoxia in river water are driven by catchment inflows and stratification (Scicluna et al, 2015). Seasonal hypoxia in shallow rivers may be induced by pollution inputs, seasonal rainfall, and temperature (Wang et al, 2016).…”
Section: Tablementioning
confidence: 99%
“…Site S3 was chosen for an in-depth study of the relationships between the variables. Unlike lakes and estuaries, hypoxia and anoxia in river water are driven by catchment inflows and stratification (Scicluna et al, 2015). Seasonal hypoxia in shallow rivers may be induced by pollution inputs, seasonal rainfall, and temperature (Wang et al, 2016).…”
Section: Tablementioning
confidence: 99%
“…4) is consistent with increased hypoxia in this period (Zillen and Conley, 2010). A key effect of this would be to enhance the release of phosphorus from the sediment, which is a key driver of N. spumigena blooms in the Gippsland Lakes (Cook et al, 2010;Scicluna et al, 2015).…”
Section: Cyanobacteria Blooms and Eutrophicationmentioning
confidence: 99%
“…The generally lower sediment δ 15 N values prior to 1870 (below 130 cm) are consistent with this. Second, cyanobacterial blooms are driven by a focused release of phosphorus from the sediments during bottom water hypoxia or anoxia, and it was estimated that a large recent bloom of N. spumigena was caused by a release of ∼ 25 t of phosphorus from the sediment in Lake King (Scicluna et al, 2015). Given that phosphorus is trapped and effectively recycled in periodically anoxic and high residence time systems such as the Gippsland Lakes, it is plausible that a pre-European phosphorus catchment load of 50 t per year could maintain blooms of at least the same magnitude as currently observed (Grayson et al, 2001).…”
Section: Cyanobacteria Blooms and Eutrophicationmentioning
confidence: 99%
“…We have previously shown that the primary source of phosphorus fuelling summer blooms of N-fixing cyanobacteria was from the sediment (Scicluna et al, 2015;Zhu et al, 2016). This sediment release of phosphorus was induced by hypoxia, which was in turn driven by internal primary production.…”
Section: Internal Nutrient Dynamicsmentioning
confidence: 99%
“…High primary production as a result of eutrophication can lead to hypoxia or anoxia in poorly mixed bottom water and subsequently enhance the recycling of both nitrogen and phosphorus, which again can reinforce eutrophication (Correll, 1998). This has been found in many stratified estuarine systems around the world, including the Baltic Sea (Vahtera et al, 2007) and the Black Sea (Capet et al, 2016), the Neuse River Estuary (Paerl et al, 1995), and the Gippsland Lakes (Scicluna et al, 2015). The magnitude of sediment phosphorus release is related to severity of bottom-water dissolved oxygen (DO) depletion as well as the duration of hypoxia and/or anoxia.…”
Section: Introductionmentioning
confidence: 97%